Answer:
![y=-(x-1)^2+2](https://img.qammunity.org/2023/formulas/mathematics/college/r6m893hfn0gqzbxumv9rd3n783yu05nvy7.png)
Explanation:
A quadratic function in vertex form is represented as:
![\begin{gathered} y=a(x-h)^2+k \\ \text{where,} \\ (h,k)\text{ is the vertex} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cls6jod5qjp476r9zu2kssjs5ay00pss15.png)
Given the vertex (1,2) substitute it into the function:
![y=a(x-1)^2+2](https://img.qammunity.org/2023/formulas/mathematics/college/5isubva96xtro4vzl2b2xsoo2ve58tdcrz.png)
As you can see, we still do not know the value for ''a'', use the point given (4,-7) substitute it (x,y) and solve for ''a'':
![\begin{gathered} -7=a(4-1)^2+2 \\ -7=a(3)^2+2 \\ -7=9a+2 \\ 9a=-7-2 \\ a=-(9)/(9) \\ a=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6w7byfa3zob37tvzyssjlekppti0ndbco9.png)
Hence, the equation of the function would be:
![y=-(x-1)^2+2](https://img.qammunity.org/2023/formulas/mathematics/college/r6m893hfn0gqzbxumv9rd3n783yu05nvy7.png)